Evaluation of (Tinomiscium petiolare Hook.F. &Thomson) Extract Ointment on Inflammation and Angiogenesis During Incision Wound Healing - Larantika Hidayati; Iqlila Romaidha; Anas Fadli Wijaya; Ade Sucipto; Eko Budi Laksono (Indonesian Journal of Global Health Research, 2025)
Wound incidence remains high worldwide and includes surgical injuries, burns, ulcers and trauma. National reports also show that abrasions and contusions account for more than half of wound complaints. These data indicate a continuing need for effective therapeutic approaches. Wound healing depends on a regulated inflammatory phase and sufficient angiogenesis, and disturbances in these processes can delay tissue repair. Natural compounds with anti-inflammatory and pro-angiogenic activity offer potential support. Tinomiscium petiolare contains flavonoids and alkaloids with documented roles in modulating inflammation and promoting vascular growth. Evidence regarding its effects on incision wounds is limited and requires systematic evaluation. This study aimed to evaluate the wound-healing effects of Tinomiscium petiolare extract ointment by examining inflammatory and angiogenic responses in incision wounds with and without Staphylococcus aureus infection. Twenty-four male Rattus norvegicus were randomized into four groups consisting of non-infected controls, infected controls, extract-treated non-infected rats and extract-treated infected rats. Standardized incision wounds were created, infection was induced in designated groups and the extract ointment was applied to treatment groups. Tissue samples were collected on days 3 and 7 to measure TNF-α expression, macrophage infiltration and blood vessel formation. Statistical analysis included normality testing, variance homogeneity testing and comparative analyses with post-hoc procedures when required. TNF α levels showed no group differences on day 7. Temporal analysis demonstrated significant reductions from day 3 to day 7 in T3 and T4 (p < 0.05). Macrophage infiltration differed among groups (p = 0.044), and post-hoc analysis indicated significantly lower macrophage counts in T4 compared with T1 after Bonferroni correction. Blood vessel density also varied among groups (p = 0.019), and temporal evaluation showed a progressive increase in angiogenesis in T4 from day 3 to day 7, although pairwise comparisons did not reach statistical significance. The extract modulated inflammatory activity and supported angiogenic progression, with the strongest effects in infected wounds treated with the ointment.